Neuromuscular adaptations induced by low load resistance training method with skin cooling - Sugawara, H.; Tadano, C.; Macdonald, G.; Asami, S.; Shimose, R.; Muro, M. (Japanese Journal of Physical Fitness and Sports Medicine, 2013)
Loss of muscle strength is not only associated with loss of muscle mass, but also affected by neural factors. It is well known that facilitatory and inhibitory responses of spinal motor neurons occur with cutaneous stimulation via spinal interneurons. The purpose of this study was to examine the neural adaptations associated with low load resistance training utilizing skin cooling (SC). 10 men trained both legs and each side was randomly assigned to SC training (SC-T) and non SC training (NSC-T). Subjects performed 30 isometric ankle dorsiflexion repetitions at 35% maximum voluntary contraction (MVC) 3 times weekly for 6 weeks. The skin cooling condition was defined as when skin temperature was 25°C while repetitive resistance training was being performed. Dorsiflexor MVC significantly increased in both SC-T (n = 9) and NSC-T (n = 9) by 12.8 and 3.8%, respectively. A significant increase in root mean square of EMG (rmsEMG) was observed for 30 isometric ankle dorsiflexion repetitions in SC-T both pre- and post-training. Lower leg girths did not significantly increase post-training. Therefore, the results of this study suggest that muscle strength might increase via changes in neural activation and that SC-T may lead to greater increases in muscle strength compared with NSC-T because of improved muscle activation during resistance training with SC. Therefore, we suggest that low load resistance training with SC is an effective method to increase muscle strength.